Chimeric antigen receptor T-cell therapy for the treatment of lymphoid malignancies: is there an excess risk for infection?. Issue 3 (March 2021) - Gudiol, Carlota; Lewis, Russell E; Strati, Paolo; Kontoyiannis, Dimitrios P
Summary: Therapy with genetically engineered chimeric antigen receptor (CAR) T cells targeting the CD19 antigen is promising for a number of refractory or relapsed B-cell malignancies. Information on the infectious complications of this immunotherapeutic strategy is scarce and difficult to interpret, as many factors influence infection incidence and outcomes. CAR T-cell therapy is usually given to patients with haematological cancers who have been heavily pretreated and are severely immunosuppressed. Moreover, the risk of infection is increased by the administration of lymphodepleting chemotherapy before CAR T-cell infusion, and by the development of complications such as cytokine release syndrome or immune effector cell-associated neurotoxicity syndrome, which are managed with anti-interleukin-6 antibodies, or corticosteroids, or both. On-target, off-tumour toxicities, such as B-cell aplasia, hypogammaglobulinaemia, and persistent or biphasic cytopenia, are common. In this Review, we evaluate the reported infectious complications of CAR T-cell therapy and associated risk factors and offer perspectives on its infection risk.